Determinants of User Satisfaction in BRImo - Nuraini, N.; Hamid, Rahmad Solling; Jasman, Jumawan (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the effects of psychological trust and service innovation on user satisfaction with the BRImo mobile banking application, with Perceived of usefulness serving as a mediating variable. Psychological trust is defined as users’ confidence in the security, reliability, and integrity of the application system, while service innovation refers to users’ perceptions of feature updates, service creativity, and the application’s ability to adapt to their needs.This research employs a quantitative approach by developing an extended Technology Acceptance Model (TAM). Data were collected through an online survey of 200 active BRImo users and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that psychological trust and service innovation have positive and significant effects on Perceived of usefulness. Perceived of usefulness also has a significant effect on user satisfaction. Furthermore, Perceived of usefulness partially mediates the relationship between psychological trust and user satisfaction, but does not mediate the relationship between service innovation and user satisfaction. These findings suggest that BRImo user satisfaction is influenced not only by the functional benefits of the application but also by users’ trust in system security and the directly experienced innovative features. Practically, this study highlights the importance of strengthening system security and reliability, as well as continuously developing service innovations to enhance mobile banking user satisfaction in Indonesia. Theoretically, this study enriches the development of TAM by integrating psychological and innovative factors within the context of digital banking.